2019
DOI: 10.1021/acs.jafc.9b01115
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antioxidant Peptides Purified from Mulberry (Morus atropurpurea Roxb.) Leaf Protein Hydrolysates with Hemolysis Inhibition Ability and Cellular Antioxidant Activity

Abstract: Neutrase-hydrolysates hydrolyzed from mulberry leaf proteins were separated by ion exchange chromatography, gel filtration chromatography, and semipreparative reverse-phase HPLC. Purified fractions were analyzed for their radical scavenging activity, hemolysis inhibition ability, and cellular antioxidant activity (CAA). Three new antioxidant peptides, P1 (SVL, 317 Da), P2 (EAVQ, 445 Da), and P3 (RDY, 452 Da), were obtained from the most active HPLC fraction (R1) and identified using UPLC-QTOF-MS. These three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 43 publications
1
48
0
Order By: Relevance
“…Cuttlefish-purified peptides can obviously inhibit the oxidation process of linoleic acid, effectively protect the DNA damage induced by • OH radicals, and have no toxic effect to cells at higher concentrations [ 159 ]. In addition, some studies have confirmed that PAs have certain potential in the treatment of cancer [ 275 ], malaria [ 276 ], hypertension [ 277 , 278 ] and blood diseases [ 224 ], and are expected to become therapeutic drugs. Bioactive peptides derived from rapeseed protein (LY, RALP, GHS) can significantly inhibit the secretion of NO, il-6 and tumor necrosis factor stimulated by lipopolysaccharide, and then repair the damage of spontaneously hypertensive cells caused by oxidative stress, which has potential application value in protecting the body from oxidative and inflammatory damage [ 279 ].…”
Section: Potential Application Of Food-derived Pasmentioning
confidence: 99%
“…Cuttlefish-purified peptides can obviously inhibit the oxidation process of linoleic acid, effectively protect the DNA damage induced by • OH radicals, and have no toxic effect to cells at higher concentrations [ 159 ]. In addition, some studies have confirmed that PAs have certain potential in the treatment of cancer [ 275 ], malaria [ 276 ], hypertension [ 277 , 278 ] and blood diseases [ 224 ], and are expected to become therapeutic drugs. Bioactive peptides derived from rapeseed protein (LY, RALP, GHS) can significantly inhibit the secretion of NO, il-6 and tumor necrosis factor stimulated by lipopolysaccharide, and then repair the damage of spontaneously hypertensive cells caused by oxidative stress, which has potential application value in protecting the body from oxidative and inflammatory damage [ 279 ].…”
Section: Potential Application Of Food-derived Pasmentioning
confidence: 99%
“…The RSA of the gallate ester derivatives against the stable DPPH ⋅ was determined spectrophoto‐ metrically [39,40] . The methods of Casimir and Wang et al .…”
Section: Methodsmentioning
confidence: 99%
“…In the majority of cases, the common cell lines used include: human epithelial colorectal adenocarcinoma (Caco-2) (Zhang, Tong, et al, 2019;Tonolo et al, 2020), human liver carcinoma (HepG2) (Chen et al, 2019;Sun et al, 2019), human normal hepatoma (Chang) (Je et al, 2015;Ding et al, 2019), cervical adenocarcinoma (HeLa) (Ma et al, 2016;Mart ınez-Leo et al, 2019), human umbilical vein endothelial (HUVEC) (Liang et al, 2018;Xu et al, 2018), human neuroblastoma (SH-SY5Y) (Lee & Hur, 2019;Sheng et al, 2019), rat adrenal pheochromocytoma (PC12) (Lee & Hur, 2019;Liu et al, 2019) and mouse macrophage (RAW 264.7) (Saisavoey et al, 2016;Indiano-Romacho et al, 2019) cells. Also, the most common inductor of oxidative stress used in the above-mentioned studies was hydrogen peroxide (H 2 O 2 ), a reactive oxygen species (ROS), because it can rapidly diffuse across cell membranes and can trigger programmed cell death (Di Marzo et al, 2018).…”
Section: Mammalian Cell Line Models Used To Evaluate Cellular Antioxidant Activitymentioning
confidence: 99%
“…Yang, Li, et al (2017) purified two peptides (KWFCT and Ac-QWFCT) from 3-10 kDa peptide fraction from pine nut (Pinus koraiensis) meal protein hydrolysate with cellular antioxidant activity (612.8 and 916.3 µM quercetin equivalents/100 g, respectively). Similarly, Sun et al (2019) synthesised three peptides (SVL, EAVQ and RDY) derived from Mulberry (Morus atropurpurea Roxb.) leaf protein hydrolysate that exhibited cellular antioxidant activity (1706, 1501 and 2204 lM quercetin equivalents/100 g peptide, respectively).…”
Section: Mammalian Cell Line Models Used To Evaluate Cellular Antioxidant Activitymentioning
confidence: 99%